Logging In Java with the JDK 1.4 Logging API and Apache log4j - Gupta, Samudra (Apress, 2012)
This book deals with the concept of building a flexible and robust application logging framework for Java-based applications. After an introduction to application logging, this book covers the two most popular Java-based logging APIs: the JDK 1.4 logging API and Apache log4j version 1.2.6. The text provides a comprehensive study of these two APIs, and in the final chapter you will find a comparative study of the two logging APIs and a few best practices for using them.